Dasatinib enhances curcumin-induced cytotoxicity, apoptosis and protective autophagy in human schwannoma cells HEI-193: The role of Akt/mTOR/p70S6K signalling pathway - Pang Pengfei; Zhang Shirong (Acta Pharmaceutica)
The present study was carried out in human schwannoma cells (HEI-193) to determine the combined anti-cancer effect of curcumin and dasatinib. Cells were treated with curcumin only, dasatinib only, or the combination of curcumin and dasatinib for 24 hours. Cellular toxicity, cell proliferation, and cell death were determined by LDH, MTT, and trypan blue dye assays, respectively. ELISA based kit was used to determine apoptotic cell death. Western blotting was used to determine the expression of apoptotic and autophagy-associated protein markers. Similarly, expression levels of Akt/mTOR/p70S6K signalling pathway-related proteins were studied using Western blotting. Cell death and apoptosis were significantly higher in HEI-193 cells treated with curcumin and dasatinib combination compared to individual controls. The combination of curcumin and dasatinib significantly enhances autophagy markers compared to individual controls. Furthermore, the combination of curcumin and dasatinib significantly activates Akt/mTOR/p70S6K signalling pathway compared to individual controls. In conclusion, our results suggest that the combination of curcumin and dasatinib significantly enhances cytotoxicity, apoptosis, and protective autophagy in HEI-193 cells through Akt/mTOR/p70S6K signalling pathway.